Reflection on the leadership practice of Saul as a failure of leadership for church pastors - Ming, D. (Acta theologica, 2022)
privileged to be the first king of Israel. Samuel was opposed to the idea of having a king as he saw this as a rejection of himself and of God’s rule over Israel.However, God instructed Samuel to comply with the people’s request to have a king, but to inform them of how the king would conduct himself. Nevertheless, the people had made up their minds, and they would not let anything stop them from getting what they wanted (1 Samuel 8:11-20). God was not surprised by this. Saul was crowned king of Israel by Samuel. Saul was taller and handsomer than all of the Israelites. He seemed to be doing well until he started making mistakes. These mistakes led to his rejection by God, and to his suicide at Mount Gilboa during the fight against the Philistines (1 Samuel 31:4). Saul’s leadership may be an example of a failure of leadership for church pastors of today. This article aims to describe the failure of Saul in leading the nation of Israel and to provide an example for church leaders of today. Through the analysis of Saul’s leadership, a reflective analysis may be formed so that a transformation leadership model can be developed for pastors and church leaders. The study follows a descriptive qualitative approach, with a literature study.After observing the results of the leadership practice of Saul as a failure of leadership, researchers can develop a constructive reflection for the transformation leadership model: 1) to manage a vision for the church pastors of today, 2) to transform an interaction with God, and 3) to be persistent in mission for church pastors of today.